Phylogeny and Geographic History of Annonaceae - Doyle, James; Le Thomas, Annick (Géographie physique et Quaternaire, 1997)
ABSTRACTWhereas Takhtajan and Smith situated the origin of angiosperms between Southeast Asia and Australia, Walker and Le Thomas emphasized the concentration of primitive pollen types of Annonaceae in South America and Africa, suggesting instead a Northern Gondwanan origin for this family of primitive angiosperms. A cladistic analysis of Annonaceae shows a basal split of the family into Anaxagorea, the only genus with an Asian and Neotropical distribution, and a basically African and Neotropical line that includes the rest of the family. Several advanced lines occur in both Africa and Asia, one of which reaches Australia. This pattern may reflect the following history: (a) disjunction of Laurasian (Anaxagorea) and Northern Gondwanan lines in the Early Cretaceous, when interchanges across the Tethys were still easy and the major lines of Magnoliidae are documented by paleobotany; (b) radiation of the Northern Gondwanan line during the Late Cretaceous, while oceanic barriers were widening; (c) dispersal of African lines into Laurasia due to northward movement of Africa and India in the Early Tertiary, attested by the presence of fossil seeds of Annonaceae in Europe, and interchanges between North and South America at the end of the Tertiary.